The Village Potential Development in The Made Village, Jombang, in Improving The Welfare and Independence of The Community - Novy Setia Yunas; Mi’rojul Huda (Institute for Research and Community Services, 2018)
The ability and freedom without opportunities would make people in the countryside remain poor. The aim of this community service was to provide facilitation and direction to make a community or a group become empowered, independent, and prosperous. This empowerment program used lecturing and training/workshop approach, as well as mentoring and mentoring by providing experience and direct assignments to groups of gadung crisps craftsmen, PKK and dasawisma. The results of this community service showed that the potential possessed by the Made Village community is quite large. Unfortunately some government policies were considered not right on target, and the lack of access and information made the skills of the community unable to develop optimally. The results of this program which took the form of a smart home program in the field of education, the branding of Srikandi Made in the field of women's empowerment and the environment, as well as the marketing management knowledge of chipmakers in the field of microeconomics, are considered to be able to become a model for the development of villages that can give a new nuance in developing the village potential and the most important economic, social and educational impact on the community in Made Village.